Librarians and Technology Evangelism. Issue 1 (2nd April 2016) - Coltrain, Mark
ABSTRACT: Being advocates, or evangelists, for certain tools is not a new idea for many librarians in terms of promoting our digital resources. However, what is new is our involvement in promoting digital technologies used for teaching and engagement to faculty and other college stakeholders. In addition, our role has expanded to working with those stakeholders to both understand the purpose and use of the tools and to create best practices for using them in a variety of learning environments. This article recounts the experiences of one librarian with this approach at Central Piedmont Community College in Charlotte, North Carolina.